PENGARUH MODEL PEMBELAJARAN CREATIF PROBLEM SOLVING TERHADAP AKTIVITAS DAN HASIL BELAJAR KOMPUTER JARINGAN DASAR MATERI PERAKITAN KOMPUTER SISWA KELAS X TKR SMK NEGERI 3 KOTABUMI T.A. 2019-2020 - Benediktus Hely Purwanto (Sienna, 2020)
The purpose of this research is to determine the effect of using creative problem solving learning models on student learning activities and outcomes. The research was conducted in the form of Classroom Action Research and consisted of 2 cycles and was carried out on class X TKR students at SMK Negeri 3 Kotabumi North Lampung. Each cycle is divided into a planning stage, an implementation stage, an observation stage and a reflection stage. The level of success of this study if it has reached the specified standard of success indicators, namely the mean score of student activeness> 75% and students' classical completeness> 75% in one class. After carrying out research and data processing, results showed an increase in the level of activeness and learning outcomes of students' computers in basic network computer subjects. This situation is shown from the level of student activity increased by 16% and student completeness in the pre-cycle by 22% increased to 63% in cycle I and so on to 83% in cycle II.